Constraining the oligopoly manipulation in electricity market: A vertical integration perspective. (1st March 2020) - Guo, Hongye; Chen, Qixin; Zhang, Yan; Liu, Kai; Xia, Qing; Kang, Chongqing
Abstract: In the recent years, the electricity market deregulation reforms are prevalent in many countries, bringing about the problem of market power abuse. As a typical property right structure transformation approach, the vertical integration has rarely been considered and analyzed as a countermeasure towards market power abuse problem. Facing the diverging attitudes on the vertical integration around the world, the problems of whether the vertical integration should be allowed in the wholesale market still remains vague. Thus, the paper proposes a framework to analyze the decision scheme of vertically integrated companies and their corresponding impacts on the market operation. The model is built in the bilevel format, with the consideration on the particularities of electricity markets. The nonlinear model is then transformed into the linearization format. Based on the real generation mix data in Guangdong province, China, the market equilibrium with/without vertical integration is presented, combined with the analysis on the market clearing price, social welfare, and profit allocation. Finally, the policy suggestions on the vertical integration in the deregulated electricity market is proposed. Highlights: Decision schemes of vertically integrated company in power markets are formatted. Non-vertically-integrated companies with large shares likely exercise market power. The introduction of vertical integration will help to achieve Pareto improvements. The mismatch between generation & retail shares is a key for market power exercise.